Zwischenruf – przegląd stanowisk badawczych - Czartoryski, Adam S. (Wydawnictwo Uniwersytetu Rzeszowskiego, 2020)
The purpose of this article is to present the most important theories and works related to zwischenruf (heckling) over the years, which are actually the current state of research. The vast majority of them are based on research in the German language area, which have made the biggest steps in this respect, paving the way for research in other languages and which form the basis for any subsequent research on zwischenruf (heckling), both in a general and detailed sense, i.e. in the context of studies on parliamentary interruptions. The article is based mainly on German examples, which I justify with the desire to expand and enrich the state of knowledge of Polish-language researchers, including linguists. At the same time, however, where necessary and justified, I also refer to Polish and other foreign theories and works.
Keywords: heckling; politolinguistics; interruptions; political language